Knowledge Mapping of Research on Internal Control in Government: A Bibliometric Analysis - Hadiyanti, Endang; Jannah, Lina Miftahul; Lutfi, Achmad (International Journal Labs, 2024)
The interest in the concept of internal controls system has been growing consistently over the past few years to study the use and the effectivity of this system, particularly in government. Yet, a comprehensive and updated review of this field is still lacking. In this paper, we use bibliometric analysis and VOSviewer software to investigate the research related to the government internal control. Focusing on publications in journals indexed in the Scopus database, we conducted a quantitative bibliometric analysis from 1970 to 2023 and found 397 journal articles. Result shows that it has grown considerably in the last few years. We were also able to identify the authors, journals, nations or regions, and citation counts that helped to grow the body of research on this topic. Indonesia is the nation with the greatest number of published documents related to the topic, followed by China, the United States, and other countries. According to the author's keywords, accountability, control, ethics, fraud, governance, Malaysia, and performance have all received a lot of attention. In the end, we draw the conclusion that more interdisciplinary research is required to gather information and to improve the study by employing different analytical tools.